2018
DOI: 10.3171/2017.8.jns171167
|View full text |Cite
|
Sign up to set email alerts
|

Pterional versus superciliary keyhole approach: direct comparison of approach-related complaints and satisfaction in the same patient

Abstract: OBJECTIVE The objective of this study was to evaluate and compare the level of patient satisfaction and approach-related patient complaints between a superciliary keyhole approach and a pterional approach. METHODS Patients who underwent an ipsilateral superciliary keyhole approach and a contralateral pterional approach for bilateral intracranial aneurysms during an 11-year period were contacted and asked to complete a patient satisfaction questionnaire. The questionnaire covered 5 complaint areas related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…As shown in previous studies, cosmetic results matter to patients, especially in the frontotemporal region. 14 , 26 It has been shown that even a dent or irregularity of the cranioplasty may jeopardize the success of the surgery. 26 It was discovered that TCUS imaging may be painful within the first days after surgery, which is explained by the postoperative pain over the wound incision, and should be kept in mind when performed at bedside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in previous studies, cosmetic results matter to patients, especially in the frontotemporal region. 14 , 26 It has been shown that even a dent or irregularity of the cranioplasty may jeopardize the success of the surgery. 26 It was discovered that TCUS imaging may be painful within the first days after surgery, which is explained by the postoperative pain over the wound incision, and should be kept in mind when performed at bedside.…”
Section: Discussionmentioning
confidence: 99%
“…The questions were modified on the basis of a previous publication by Park et al. 14 In addition, patients who had a bypass surgery before were asked to comment on overall cosmetic result compared with the PMMA implant.…”
Section: Methodsmentioning
confidence: 99%
“…Park et al 21) conducted a patient satisfaction survey on 21 patients who underwent an ipsilateral superciliary keyhole approach and contralateral pterional approach for bilateral intracranial aneurysms. When asked about the cosmetic results for the supraorbital approach vs. the pterional approach, 76.2% of the patients complained about the cosmetic results for the pterional approach side due to a loss of frontal hair along the operative scar, disfiguring scar, and anterior temporal hollow, whereas only 14.3% of the patients had minor cosmetic complaints for the supraorbital approach side due to the operative scar.…”
Section: Cosmetic Resultsmentioning
confidence: 99%
“…After achieving the surgical goal, the patient satisfaction level is affected by the invasiveness of the surgical approach. When patients who underwent both an ipsilateral supraorbital keyhole approach and a contralateral pterional approach for bilateral aneurysms were asked to compare their experience, their overall satisfaction level was significantly higher for the supraorbital keyhole approach 21) . As regards their ptrional experience, the complaint scores were higher for the cosmetic results, palpable cranial irregularities, and craniotomy-related pain at or around the bone flap.…”
Section: Patient Satisfaction After Supraorbit-al Keyhole Approachmentioning
confidence: 99%
See 1 more Smart Citation